Viability estimation and morphological characterization of pollen Datura suaveolens Willd (Solanaceae) - Bispo, R. B.; Santos, L. C. B.; Santos, J. F. L.; Karsburg, I. V. (Scientific Electronic Archives, 2018)
The species Datura suaveolens W. belongs to the family Solanaceae. It is a natural shrub species of the Himalayas, is widely distributed in South America and Brazil. In Brazil it is cultivated for medicinal and ornamental purposes. The objective of this work was to perform the morphological characterization and verify the pollen viability of the D. suaveolens species by means of colorimetric tests in order to determine the best dye for the species. Flower buds of Datura suaveolens were collected with occurrence in the municipality of Alta Floresta, MT. The experiment was carried out at the Cytogenetic and Tissue Culture Laboratory at the State University of Mato Grosso, Alta Floresta University Campus. For the estimation of pollen viability, three different dyes were evaluated: lugol, Alexanderâ€™s reactive and acetic orcein. For the pollen morphology, forty pollen grains stained with 3% safranin were analyzed. The morphological parameters analyzed were: equatorial diameter, polar diameter, size and shape and opening of the pollen grains. The diameter measurements were measured with the help of ImageJ software. The Alexanderâ€™s reactive is the most recommended colorimetric method for the pollen viability analysis of Datura Suaveolens because it revealed the highest average of viable pollen and presents a better visual distinction between viable and non-viable pollen. The Datura Suaveolens species has large pollen grains with Oblate-Spheroidal shape, the opening of the pollen is 3-pore type. The mean polar diameter of the species is 70.99 Î¼m and the equatorial diameter is 67.94 Î¼m. Â